1998
DOI: 10.1021/jf980185h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Pesticides into Soils from Clay−Polymer Formulations

Abstract: Alachlor was released from a controlled-release formulation (CRF) when applied to a sandy loam soil under conditions of constant temperature and moisture and achieved concentrations of 0.1−0.2 mg/kg after 1 week. Soil concentrations of 0.2−0.8 mg/kg were maintained for at least an additional 8 weeks. A large portion (35−70%) of the active ingredient was still present in the CRFs at the conclusion of the experiment. Application of alachlor as the commercial formulation resulted in 50% dissipation after only 3−4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
74
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 24 publications
4
74
0
3
Order By: Relevance
“…To the best of our knowledge, few papers have been reported to utilize such inorganic NPs alone and/or combined with organic ingredient for plant protection. Therefore, it is meaningful to investigate the pesticidal behaviors of the inorganic NPs or their formulations to reduce harmful organic pesticide usage, enhance durability and efficiency as well as overcome the physiological resistance of the pests [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, few papers have been reported to utilize such inorganic NPs alone and/or combined with organic ingredient for plant protection. Therefore, it is meaningful to investigate the pesticidal behaviors of the inorganic NPs or their formulations to reduce harmful organic pesticide usage, enhance durability and efficiency as well as overcome the physiological resistance of the pests [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been employed to obtain CRFs: alginate encapsulation (Gerstl et al, 1998), cyclodextrin complexation (Loukas et al, 1994), polymeric microcapsules (Dailey et al, 1993), lignin entrapment (Ferraz et al, 1997), and starch encapsulation (Mervosh et al, 1995). This latter was essayed for norflurazon (Boydston, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have also prepared formulations based on polyoxoaluminum-pillared clays. The release of alachlor from an Al-pillared clay CRF and its subsequent transport in soil columns showed that pillared clays can be used for controlled release of herbicides (Gerstl et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…e use of slow release formulations has been proposed as an e cient strategy to reduce the environmental impact of soil-applied pesticides. Bene cial e ects related to the use of slow release formulations include reduced mobility of the active ingredient, reduction in the amount of chemical required for pest control, savings in manpower and energy by reducing the number of applications required in comparison with conventional formulations, increased safety for the pesticide applicator, and a general decrease in nontarget e ects (Gerstl et al, 1998). Organoclays, that is, natural clay minerals with their original inorganic exchange cations replaced with organic cations, have been proven to be very good adsorbents for di erent classes of pesticides and, accordingly, have been proposed as carriers for the design of slow release formulations of pesticides (El-Nahhal et al, 2001;Hermosín et al, 2001;Prost and Yaron, 2001;Lagaly, 2001;Carrizosa et al, 2003;Cornejo et al, 2008).…”
mentioning
confidence: 99%